1997
DOI: 10.1002/(sici)1097-0215(19971104)73:3<356::aid-ijc9>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Prevailing papillomavirus types in non‐melanoma carcinomas of the skin in renal allograft recipients

Abstract: The role of human papillomavirus (HPV) in the aetiology of in situ and invasive carcinoma of the genital tract is well established. In the rare disorder epidermodysplasia verrucifor-mis (EV), in which patients develop extensive warts of unusual types and multiple cutaneous squamous cancers on light-exposed skin, current evidence suggests a probable role for a specific group of EV HPVs in the carcinogenic process. Determination of the possible role of HPV in the aetiology of non-melanoma skin cancers (NMSCs), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
99
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(114 citation statements)
references
References 0 publications
11
99
0
4
Order By: Relevance
“…DL285, accession number Z95968 (77% homology to HPV 9), and DL287, accession number Z95969 (74% homology to HPV 24), were previously described by De Villiers et al 38 This study was approved by our institutional review board.…”
Section: Hpv Genotype Accession Numbersmentioning
confidence: 99%
“…DL285, accession number Z95968 (77% homology to HPV 9), and DL287, accession number Z95969 (74% homology to HPV 24), were previously described by De Villiers et al 38 This study was approved by our institutional review board.…”
Section: Hpv Genotype Accession Numbersmentioning
confidence: 99%
“…In den malignen und prämalignen Hautveränderungen organtransplantierter Patienten sind DNA-Sequenzen einer Vielzahl unterschiedlicher humaner Papillomaviren nachweisbar [85,86,87]. Unter Verwendung sensitiver "broad range nested PCR-Techniken" ist die Diagnoserate HPV-positiver Tumore deutlich erhöht worden [88].…”
Section: Infektionen Mit Humanen Papillomaviren (Hpv)unclassified
“…Die direkte pathogenetische Relevanz potenziell onkogener Virusinfektionen ist bis heute nicht eindeutig geklärt. Für eine Beteiligung humaner Papillomaviren in der Entwicklung maligner Hauttumoren spricht vor allem der Nachweis viraler DNA in bis zu 90% der kutanen Plattenepithelkarzinome transplantierter Patienten [87,99] und die Persistenz der HPV Infektion in benignen, prämalignen und malignen Hautläsio-nen bei Patienten nach Nierentransplantation [89]. Aus der Arbeitsgruppe von Alan Storey wurde kürzlich die Unterdrückung apoptotischer Prozesse durch die E6-Proteine einiger EV-assoziierter HPV-Typen beschrieben [96].…”
Section: Infektionen Mit Humanen Papillomaviren (Hpv)unclassified
See 1 more Smart Citation
“…Although no particular HPV types have been defined as predominant, the HPV types found were novel, including HPV-16, or not yet completely characterized (Forslund et al 1997;De Villiers et al 1997). On the other hand, it has been suggested that the toxic effects of chronic As exposure on the skin might be associated with HPV infection, since the rare HPV-41 was present in As-induced malignant lesions, such as squamous cell carcinomas and arsenical keratoses (Grimmel et al 1988).…”
Section: Introductionmentioning
confidence: 99%